Active Learning: Qualitative Inquiries Into Vocabulary Instruction in Chinese L2 Classrooms. (18th March 2015) - Shen, Helen H.; Xu, Wenjing
Abstract Active learning emerged as a new approach to learning in the 1980s. The core concept of active learning involves engaging students not only in actively exploring knowledge but also in reflecting on their own learning process in order to become more effective learners. Because the nonalphabetic nature of the Chinese writing system makes learning to read and write Chinese characters extremely time‐consuming for native English speakers, this qualitative study was intended to identify instructional strategies, methods, and activities for promoting active learning among beginning learners of Chinese as a second language and to investigate students' perceptions of the identified strategies, methods, and activities with regard to their effectiveness in engaging students in meaningful learning.